О происхождении могильника XIII в. у с. Каиры Херсонской области - Бубенок, О.Б. (Материалы по археологии, истории и этнографии Таврии, 1998)
К числу загадочных археологических объектов в Таврии относится грунтовый могильник начала II тыс.н.э., обнаруженный в 1953 г. Д.Я.Телегиным в северо-восточной части с.Кайры (Горностаевский район Херсонской области). Могильник находился у обрыва над р.Конкой, на левом берегу Каховского водохранилища. Тогда, удалось исследовать лишь одно погребение в неглубокой яме, прикрытой плоским камнем. A cemetery of the 13th century discovered in Cherson region, not far from the village of Kairi, is among those which are scarcely studied. The presence of stone in the structure of burial constructions is a peculiarity of this Christian necropolis. As for the problem of the origin of the cemetery near Kairi the researchers have not come to a unanimous conclusion. Some of them think that it is a Slavic monument, others failed to define its ethnographic attribution of the population who had left this object. The most admissible is a version of a Caucasian origin of Kairi cemetery. In the first half of the 13th century, the Mongol- Tatars and the majority of the Alanic population were forced to settle in the steppe of the Northern Black Sea Coast and left Kairi and synchronous plate cemeteries behind. The author assumes that probably the Caucasian Alans-Asi moved from the lower Dnieper to the steppe of the neighbouring Crimean peninsula.